Vestibular reflexes in essential tremor: abnormalities of ocular and cervical vestibular-evoked myogenic potentials are associated with the cerebellum and brainstem involvement - BAL, NİLÜFER (My University, 2023)
This study utilized cervical vestibular-evoked myogenic potentials tests (cVEMP) and ocular vestibular-evoked myogenic potentials tests (oVEMP) to investigate the vestibulocollic and vestibuloocular refex arcs and to evaluate cerebellar and brainstem involvement) in essential tremor (ET). Eighteen cases with ET and 16 age- and gender-matched healthy control subjects (HCS) were included in the present study. Otoscopic and neurologic examinations were performed on all participants, and both cervical and ocular VEMP tests were performed. Pathological cVEMP results were increased in the ET group (64.7%) compared to the HCS (41,2%; p>0.05). The latencies of P1 and N1 waves were shorter in the ET group than in HCS (p=0.01 and p=0.001). Pathological oVEMP responses were signifcantly higher in the ET group (72.2%) compared to the HCS (37.5%; p=0.01). There was no statistically signifcant diference in oVEMP N1-P1 latencies between groups (p>0.05). Because the ET group had high pathological responses to the oVEMP, but not the cVEMP, the upper brainstem pathways may be more afected by ET.
Keywords: Vestibulocollic refex; Vestibuloocular refex; cVEMP; oVEMP; Essential tremor